Acupressure to Reduce Treatment-Related Symptoms for Children With Cancer and Recipients of Hematopoietic Stem Cell Transplant: Protocol for a Randomized Controlled Trial. (August 2019) - Lown, E Anne; Banerjee, Anu; Vittinghoff, Eric; Dvorak, Christopher C; Hartogensis, Wendy; Melton, Alexis; Mangurian, Christina; Hu, Hiroe; Shear, Deborah; Adcock, Robyn; Morgan, Michael; Golden, Carla; et al.
Background: We describe the study design and protocol of a pragmatic randomized controlled trial (RCT) Acupressure for Children in Treatment for a Childhood Cancer (ACT-CC). Objective: To describe the feasibility and effectiveness of an acupressure intervention to decrease treatment-related symptoms in children in treatment for cancer or recipients of a chemotherapy-based hematopoietic stem cell transplant (HSCT). Design: Two-armed RCTs with enrollment of 5 to 30 study days. Setting: Two pediatric teaching hospitals. Patients: Eighty-five children receiving cancer treatment or a chemotherapy-based HSCT each with 1 parent or caregiver. Intervention: Patients are randomized 1:1 to receive either usual care plus daily professional acupressure and caregiver delivered acupressure versus usual care alone for symptom management. Participants receive up to 20 professional treatments. Main Outcome: A composite nausea/vomiting measure for the child. Secondary Outcomes: Child's nausea, vomiting, pain, fatigue, depression, anxiety, and positive affect. Parent Outcomes: Depression, anxiety, posttraumatic stress symptoms, caregiver self-efficacy, and positive affect. Feasibility of delivering the semistandardized intervention will be described. Linear mixed models will be used to compare outcomes between arms in children and parents, allowing for variability in diagnosis, treatment, and age. Discussion: Trial results could help childhood cancer and HSCT treatment centers decide about the regular inclusion of trained acupressure providers to support symptom management.